Muhammad Hatta's Economic Democracy: Analysis from an Islamic Economic Perspective - Agnes Pratiwi (Eastasouth Institute, 2025)
This study examines the relevance of Mohammad Hatta’s concept of economic democracy through the lens of Islamic economics and the maqāṣid al-sharīʿah. It departs from the persistence of structural inequality, the dominance of large capital, and limited access of lower-income groups to productive resources in Indonesia, conditions that diverge from Hatta’s vision of a people’s economy. Using a qualitative descriptive method and library research, the study analyzes Hatta’s ideas on cooperatives, people’s sovereignty over resources, and state control of strategic sectors, and maps them onto the dimensions of ḥifẓ al-māl (protection of property), ḥifẓ al-nafs (protection of welfare/life), and ḥifẓ al-ijtimā‘/al-‘adl (social justice). The findings show strong substantive alignment between Hatta’s thought and Islamic economic principles while highlighting the need to operationalize them through sharia-based cooperatives, productive zakat, and distribution-oriented fiscal policies to build a more inclusive and just economic model for Indonesia.